Rapid Identification and Monitoring of Multiple Bacterial Infections Using Printed Nanoarrays. Issue 12 (17th February 2023) - Zhang, Zeying; Sun, Yali; Yang, Yaqi; Yang, Xu; Wang, Huadong; Yun, Yang; Pan, Xiangyu; Lian, Zewei; Kuzmin, Artem; Ponkratova, Ekaterina; Mikhailova, Julia; Xie, Zian; et al.
Abstract: Fast and accurate detection of microbial cells in clinical samples is highly valuable but remains a challenge. Here, a simple, culture‐free diagnostic system is developed for direct detection of pathogenic bacteria in water, urine, and serum samples using an optical colorimetric biosensor. It consists of printed nanoarrays chemically conjugated with specific antibodies that exhibits distinct color changes after capturing target pathogens. By utilizing the internal capillarity inside an evaporating droplet, target preconcentration is achieved within a few minutes to enable rapid identification and more efficient detection of bacterial pathogens. More importantly, the scattering signals of bacteria are significantly amplified by the nanoarrays due to strong near‐field localization, which supports a visualizable analysis of the growth, reproduction, and cell activity of bacteria at the single‐cell level. Finally, in addition to high selectivity, this nanoarray‐based biosensor is also capable of accurate quantification and continuous monitoring of bacterial load on food over a broad linear range, with a detection limit of 10 CFU mL −1 . This work provides an accessible and user‐friendly tool for point‐of‐care testing of pathogens in many clinical and environmental applications, and possibly enables a breakthrough in early prevention and treatment. Abstract : A simple, fast, and accessible diagnosis tool is developed for direct point‐of‐care testing of pathogenic bacteria in clinical and food samples at the single‐cell level, by using a nanoarray‐based colorimetric biosensor. It does not need enrichment, culturing, fluorescence probes, or other sample pretreatments, and can be readily extended to many microbes such as viruses, spirochetes, mycoplasma, rickettsia, and chlamydia.